PENGEMBANGAN MULTIMEDIA INTERAKTIF MATEMATIKA BERMUATAN GAME EDUKASI PADA MATERI BANGUN RUANG KELAS VI SEKOLAH DASAR - Raharjo, Ayu Sholiha Ariyani; Rufi'i, Rufi'i; Hartono, Hartono (FKIP Unirow Tuban, 2021)
This study aims to produce interactive multimedia Mathematics containing educational games on appropriate, practical, effective, and interesting spatial building materials. This type of research is Research & Development (R&D) with the model of Lee & Owens (2004). The results of the study found that the analysis of the feasibility level was 79.64% with the